Sociologický výzkum jako podpora rozvojových projektů měst - Schmeidler, Karel; Maršálková, Kateřina (Lidé města, 2020)
In the past, architectural building activity, as well as the construction of cities in the Czech Republic, mainly took into account quantitative considerations. The disregard of quality in buildings had a negative impact in many aspects. Therefore, it is necessary to analyse the influence of the environment upon mankind, including the impact of the artificially built environment. Currently, designers are feeling the impacts of the absence of a knowledge of the humanities and social sciences. The aim of the authors was to develop scientific procedures for pre-project and project preparation in the domains of architecture, town-planning, and the environment. They should help qualitatively raise the architectonic and urbanistic activities in a fast-changing urban world and under new socio-economic conditions. A multidisciplinary research team surveyed the possibilities of communicating the information acquired through the humanities and social sciences with respect to man and his environment, as well as the creative applications of the research methods of psychology and sociology in the environment, with an emphasis placed on data collection and evaluation. Practical applications of the acquired knowledge are found in the field of design and project preparation and in the reconstruction of existing environments such as the humanisation of housing estates, the renovation of villages, the reconstruction of central city districts, the reconstruction of degraded areas, etc.